ISO 9001:2008 Quality Management System In Education - Barirohmah Barirohmah; Subiyantoro Subiyantoro (Nazhruna: Jurnal Pendidikan Islam, 2021)
Society has very high hopes for education. With education, people hope to have a better life. Agae education is able to meet the great expectations of society, the world of education requires quality assurance to maintain the results of the implementation of education. Quality assurance in education will direct the world of education to achieve educational goals. Educational institutions are expected to be able to produce Indonesian Human Resources who are competent in their fields. Human Resources who have superior competence will bring the Indonesian nation to become a developed and great nation. Education quality assurance with the ISO 9001:2008 Quality Management System is expected to be able to maintain the quality and improve the quality of education. Increasing the quality of education will improve the quality of educational products.